Análise da abordagem e resultados da produção mais limpa em empresas do núcleo de extensão produtiva e inovação da região central do Rio Grande do Sul - Hollveg, Scheila Daiana Severo (2015)
Balancing sustainable development with high productivity is a major current challenges, especially regarding the search for alternatives and technologies focused on devising processes and products that do not generate or reduce damage to the environment. In this sense, the use of tools such as Cleaner Production (CP) can contribute to increased efficiency in the use of raw materials, water and energy by not-generation, minimization or recycling of waste and by products from the production process. Thus, the objective is to analyze CP parameters used by companies in the metal-mechanic sector of the central region of Rio Grande do Sul state, participants Productive Extension Center and Innovation (NEPI), aiming to propose future scenarios resulting from the Theory of inventing problem solving (TRIZ). From this perspective, it was found that the surveyed companies adopt CP practices although no regulation. However, there are many potential to be developed by local entrepreneurs regarding environmental issues, which also depends on public politics, society and market.